Search for top squarks in events with a Higgs or Z boson using 139 fb-1of pp collision data at √s=13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; et al. (The European physical journal. C, Particles and fields, 2020)
This paper presents a search for direct top squark pair production in events with missing transverse momentum plus either a pair of jets consistent with Standard Model Higgs boson decay into b-quarks or a same-flavour opposite-sign dilepton pair with an invariant mass consistent with a Z boson. The analysis is performed using the proton-proton collision data at $$\sqrt{s}=13$$s=13TeV collected with the ATLAS detector during the LHC Run-2, corresponding to an integrated luminosity of 139 fb$$^{-1}$$-1. No excess is observed in the data above the Standard Model predictions. The results are interpreted in simplified models featuring direct production of pairs of either the lighter top squark ($$\tilde{t}_1$$t~1) or the heavier top squark ($$\tilde{t}_2$$t~2), excluding at 95% confidence level $$\tilde{t}_1$$t~1and $$\tilde{t}_2$$t~2masses up to about 1220 and 875 GeV, respectively.